Sustainability in a global circular economy: Insights on consumer price sensitivity. (17th March 2022) - Hanumante, Neeraj C.; Shastri, Yogendra; Hoadley, Andrew
Abstract: Circular economy (CE) is seen as a way of achieving global sustainability. This study demonstrates how consumer decisions, particularly in relation to price sensitivity, have a significant influence on CE adoption and therefore on global sustainability. An integrated planetary model representing the world through 15 ecological–industrial compartments is considered. The functioning of the model is governed by food web dynamics and a macro‐economic model. A circulation industry compartment recycles used products going to waste. The consumer price sensitivity for the circulated goods is captured by considering the consumers' cumulative CE participation ( CCEP ). Different CCEP patterns are studied for a variety of consumption increase rates. The results show that greater preference for circulated goods avoided system collapse, and corresponding CCEP patterns identify the sustainable zone (TSZ). A parametric study of combinations of CCEP patterns and consumption growth rates showed that with the higher consumption growth rate (four to six times linear increase of consumption over simulation horizon), the TSZ shrinks (50%). Moreover, at higher consumption growth rates, more economic incentives are required to obtain a similar ecosystem response. Finally, at a very high level of CE adoption, the overall population becomes less wealthy. Thus, preventing the consumption growth rather than promoting the CE through subsidies is more desirable from economic and ecological perspectives.